2006
DOI: 10.1128/iai.00553-06
|View full text |Cite|
|
Sign up to set email alerts
|

Immunization with Polyamine Transport Protein PotD Protects Mice against Systemic Infection with Streptococcus pneumoniae

Abstract: The human pathogen Streptococcus pneumoniae contains genes for a putative polyamine ABC transporter which are organized in an operon and designated potABCD. Polyamine transport protein D (PotD) is an extracellular protein which binds polyamines and possibly other structurally related molecules. PotD has been shown to contribute to virulence in both a murine sepsis model and a pneumonia model with capsular type 3 pneumococci. The protective efficacy of recombinant PotD was evaluated by active immunization and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 34 publications
0
40
0
2
Order By: Relevance
“…In E. coli, disruption of lolC is lethal and prevents the release of lipoproteins from the inner membrane (26). PotF is a periplasmic binding protein of the PotFGHI system involved in putrescine import in E. coli (31), a system that has homologues required for attachment to plant cells and for full virulence in the phytopathogen Agrobacterium tumefaciens (24). Finally, OppA is an oligopeptide-binding protein of the Opp system in E. coli (14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In E. coli, disruption of lolC is lethal and prevents the release of lipoproteins from the inner membrane (26). PotF is a periplasmic binding protein of the PotFGHI system involved in putrescine import in E. coli (31), a system that has homologues required for attachment to plant cells and for full virulence in the phytopathogen Agrobacterium tumefaciens (24). Finally, OppA is an oligopeptide-binding protein of the Opp system in E. coli (14).…”
Section: Resultsmentioning
confidence: 99%
“…ABC system proteins were selected as potential vaccine candidates because members of this family of proteins have been shown generally to be immunogenic and to play roles in bacterial virulence (16). In addition, some components of ABC systems have been shown to be vaccine antigens (6,31,34,35). Homologues of the LolC, PotF, and OppA proteins identified in B. pseudomallei and soluble domains were produced in E. coli, with membrane-spanning regions removed in order to aid expression and purification for the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, proteomics analysis revealed that the secretion of PotD into environment is correlated with the formation of biofi lms in Aggregatibacter actinomycetemcomitans , causing aggressive periodontitis (Zijnge et al 2012 ). Furthermore, Shah and Swiatlo et al reported that in Streptococcus pneumoniae , which causes pneumonia, uptake of spermidine by PotABCD is important for pathogenicity in mice, and an antiPotD antibody was used in a study of infection control of S. pneumoniae (Shah and Swiatlo 2006 ). In uropathogenic Proteus mirabilis PlaP is important for putrescine uptake, swarming motility, and urothelial cell invasion.…”
Section: Studies On Pathogenic Bacteria and Polyamine Transportersmentioning
confidence: 98%
“…Although the importance of polyamine biosynthesis and transport in pneumococcal pathogenesis has been known for a number of years (15,16,31), the precise molecular role of these molecules in this important bacterial pathogen has remained elusive. We have demonstrated that pneumococci encode enzymes for the synthesis of spermidine from arginine.…”
Section: Discussionmentioning
confidence: 99%